L'Art Céramique Hadès : Céramique de Dour. - Dobbels, Jacques; Picrit, Frank (Mons : ASBL Cercle culturel 'Vieux-Nimy', 2018)
Boulmant, Georges ; Van de Spiegele, Louis ; Somville, Roger ; Tits, Simone ; Timper, Paul ; Bataille, Marie-Henriette ; Bataille, Thérèse ; Duhayon, Michel ; Cornil, Monique ; Lambert, Claire Célia ; Timper, Clara ; Brescheau, Lucien ; Jorish, George ; Brison, Jacqueline ; Johnen, M. R.
L'Atelier de Céramique de Dour. Rétrospective 2018
boek
Keywords: Dobbels Jacques